Some results related with type of family of sets - M. Jasim, Alaa; F. Al-Mayahi, Noori (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we will discuss the concept of fuzzy set and its complement , and also we will study new types of fuzzy families such as the fuzzy -field ,fuzzy - -field ,fuzzy -field ,fuzzy - -field ,and fuzzy -field and the relationship between them